The top-cited systematic reviews/meta-analyses in tuberculosis research: A PRISMA-compliant systematic literature review and bibliometric analysis. Issue 6 (February 2017) - Zhang, Yonggang; Huang, Jin; Du, Liang
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The top-cited systematic reviews/meta-analyses in tuberculosis research have not been identified. The objective of this study was to identify the 100 top-cited systematic reviews/meta-analyses in tuberculosis research, and to understand factors resulting in highly cited works, and establish trends in systematic reviews/meta-analyses in tuberculosis research. Methods: The Web of Science Core Collection was searched for systematic reviews/meta-analyses on tuberculosis up to January 31, 2016. Articles were ranked by citation count and screened by 2 authors. The following information was collected and analyzed from each included study: citation of Web of Science Core Collection, author, country, year, journal, institution, page number, and reference number. Results: The 100 top-cited studies were cited from 54 to 662 times and were published between 1997 and 2014. Ten authors have more than 1 study as the first author and 10 authors have more than 1 study as corresponding author. The country with the most top-cited studies was USA (n = 26). The institutions with the largest number of the studies were McGill University in Canada (n = 18). The studies were published in 32 journals, whereas 12 were published in PloS Medicine, followed by Lancet Infectious Diseases (n = 11). Conclusions: Developed countries and high-impact journals may publish more top-cited systematic review/meta-analysis in tuberculosis research.